1986
DOI: 10.1002/ar.1092160107
|View full text |Cite
|
Sign up to set email alerts
|

The rete ovarii of cattle and deer communicates with the uterine tube

Abstract: Textbooks in embryology, histology, and reproductive biology erroneously state that the mammalian rete ovarii consists of a tubular structure in the medulla of the ovary which is closed at both ends. In white-tailed deer and cattle, the lumen of the rete ovarii opens directly into the infundibulum near its attachment to the ovary. This serendipitous discovery followed the serial sectioning of over 100 ovaries. Secretions through this tuboretial opening may affect reproductive processes. Obstructions could expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
7
2
Order By: Relevance
“…Other parts of the fallopian tubules were not investigated immunohistologically in the present study, but the canine fallopian fimbria together with the surface epithelium and cortical tubules in the bursal structure previously described may be developed specifically. The connection between fallopian fimbria and rete ovarii in deer has been reported (Odend'hal et al. 1986); in the present study, however, these two structures indicated different immunohistochemical traits, especially in CK7 and PLAP.…”
Section: Discussioncontrasting
confidence: 62%
“…Other parts of the fallopian tubules were not investigated immunohistologically in the present study, but the canine fallopian fimbria together with the surface epithelium and cortical tubules in the bursal structure previously described may be developed specifically. The connection between fallopian fimbria and rete ovarii in deer has been reported (Odend'hal et al. 1986); in the present study, however, these two structures indicated different immunohistochemical traits, especially in CK7 and PLAP.…”
Section: Discussioncontrasting
confidence: 62%
“…An ovarian cyst may be formed from the follicle, corpus luteum, rete ovarii, or the cortical invaginations of the surface epithelium (Odend'hal et al, 1986;Clement, 1987). It is suspected that if the epithelium of ovarian cysts, immunopositive for S-100 protein in this study, arises from the rete ovarii, immunostaining with S-100 protein could provide a useful method for distinguishing the rete cysts from the other cysts.…”
Section: Discussionmentioning
confidence: 78%
“…S-100 protein has been reported to induce hormone secretion in cultured prolactin cells (Ishikawa et al, 1983). Odend'hal et al (1986) reported that the rete ovarii might respond to hormones and possibly even produce hormones. Thus, the immunostaining with S-100 protein may be a useful method for identifying the function of the rete ovarii.…”
Section: Discussionmentioning
confidence: 99%
“…The common origin and the close embryological relationship of the two structures represent the morphological basis for the occurrence of a fimbria ovarica in most female mammals and an attachment of the appendix testis or sessile hydatides to the male gonad. In female ruminants, a permanent tuboretial connection may persist throughout adult life, as has been described for the cow and whitetailed deer (Odend'hal et al 1986). In these two species, canalized extensions of the rete ovarii open directly into the infundibulum of the oviduct close to its attachment to the ovary.…”
Section: Origin and Fate Of The Infundibular Fieldmentioning
confidence: 69%